2010
DOI: 10.1583/10-3088.1
|View full text |Cite
|
Sign up to set email alerts
|

Device and Imaging-Specific Volumetric Analysis of Clot Lysis After Percutaneous Mechanical Thrombectomy for Iliofemoral DVT

Abstract: IVUS is superior to venography for detection of residual thrombus and underlying venous pathology after pharmacomechanical thrombectomy. While greater clot lysis was seen with the AngioJet system, both the AngioJet and Trellis devices resulted in excellent clinical clot lysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…An important positive trend is the fact that clinical follow-up beyond 1 year after the procedure was documented in 25 (19,21,22,(25)(26)(27)(28)(29)(30)(31)(32)(36)(37)(38)(39)(40)(41)(43)(44)(45)(46)(47)(48)(49)(50) of 28 (19,21,22,(25)(26)(27)(28)(29)(30)(31)(32)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)…”
Section: Success Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…An important positive trend is the fact that clinical follow-up beyond 1 year after the procedure was documented in 25 (19,21,22,(25)(26)(27)(28)(29)(30)(31)(32)(36)(37)(38)(39)(40)(41)(43)(44)(45)(46)(47)(48)(49)(50) of 28 (19,21,22,(25)(26)(27)(28)(29)(30)(31)(32)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)…”
Section: Success Ratesmentioning
confidence: 99%
“…To determine safety and efficacy thresholds for this review, the committee reviewed more than 200 articles and ultimately selected 30 studies that met the following criteria: (i) English-language publication from 2004-2013; (ii) reported on the endovascular thrombolytic treatment of patients with lower extremity DVT using pharmacologic CDT or PCDT; (iii) included mainly acute DVT cases; and (iv) included a prospective data collection or a retrospective review of data on at least 25 treated patients (19)(20)(21)(22). Of these 30 studies, 17 reported thrombus removal as a percentage based on review of pre-and posttreatment venograms (19,20,23,(28)(29)(30)(31)(32)35,38,(40)(41)(42)(45)(46)(47)50). In these studies, removal of more than 50% thrombus was reported in 91.8% of the 1,046 treated patients.…”
Section: Success Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be noted that residual intraluminal thrombus is a common 'obstructive lesion' in patients who have undergone thrombolysis for DVT: in one study, IVUS identified residual thrombus in 36% of patients who were felt to have normal post-thrombolysis venograms. 31 On the other hand, it is very important to note that the true clinical significance of many of the abnormalities that have been described on IVUS (especially those that are entirely occult on venography) has not been established. While lesions that clearly cause severe persistent narrowing or deform the internal architecture of the vein are likely to be significant, lesser degrees of stenosis may or may not account for an individual patient's symptoms, especially when the structure of the vein wall and lumen appear otherwise normal.…”
Section: Invasive Testingmentioning
confidence: 99%